The Iconography of Pop Culture in Ghana: Black Sherif’s Music in Perspective - Felicia Annin; Cecilia Addei (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Ghanaian tradition, like other African traditions, revolves around cultural values and beliefs. These cultural values and beliefs vary as a result of the different cultural contexts in Ghana. One of the most popular traditions in Ghana is the use of songs as a form of entertainment and a mouthpiece for satirizing society’s ills. Mohammed Ismail Sherif Kwaku Frimpong, popularly known as Black Sherif, is a musician who employs the oral genre of Ghanaian music to unveil some of the pertinent issues in Ghana. This study uses the lyrics of the selected songs as data, which are transcribed and textually analyzed to situate Black Sherif’s music as a pathway through which the young people divulge critical issues confronting them and the vulnerable in the country. The study explores how the artiste presents entertaining yet thought-provoking songs as a manner of expression and foregrounds the culture of Ghana through the use of diction, imagery, and symbolism. It argues that the young people play constitutive roles in nation-building by promoting the Ghanaian culture through the songs they write, so society should grant them an audience and heed what they say. The findings reveal that the economic situation of the country has rendered young people jobless and frustrated and that the ghetto lifestyle has emerged as a popular culture in Ghana.